2016
DOI: 10.1136/archdischild-2016-310863.481
|View full text |Cite
|
Sign up to set email alerts
|

G494(P) The use of bubble continuous positive airway pressure (bCPAP) for critically ill children in Lilongwe, Malawi

Abstract: In low resource-countries, the mortality of critically-ill children remains high. Severe pneumonia remains one of the leading causes of death. Malaria and intercurrent bacteraemia adversly affects survival in this setting. Low cost bubble continuous positive airway pressure (bCPAP) set-ups are used in some reference centres in sub-Saharan Africa. More evidence for use beyond the neonatal period is needed. We evaluated the role of bCPAP for the care of critically-ill children in Lilongwe, Malawi.This observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Four observational studies enrolled children with respiratory failure (failing standard oxygen therapy), mostly related to severe pneumonia. Mortality ranged from 33% to 55% (urban Papua New Guinea and Malawi) [ 46 , 47 , 50 ], except for one Indian study involving children with influenza-like illness during the swine flu epidemic (zero mortality) [ 44 ]. These studies reported improved respiratory signs and did not include a comparison group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four observational studies enrolled children with respiratory failure (failing standard oxygen therapy), mostly related to severe pneumonia. Mortality ranged from 33% to 55% (urban Papua New Guinea and Malawi) [ 46 , 47 , 50 ], except for one Indian study involving children with influenza-like illness during the swine flu epidemic (zero mortality) [ 44 ]. These studies reported improved respiratory signs and did not include a comparison group.…”
Section: Resultsmentioning
confidence: 99%
“…Across all these studies, older children (especially >12 months), children with HIV, severe acute malnutrition, multi-organ failure, or other comorbidities generally fared worse on CPAP that those without [ 39 , 46 , 50 ]. Early response to CPAP (specifically correction of hypoxaemia) was a strong predictor of survival [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations